The Future of School Management: Efisiensi sebagai DNA Baru Pendidikan - Azkiya Zahrul Asmi Eltsany; Jeesssy Isjtidla; Khusnul Fitriyana; Maeda Istiza; Apriliantoni Apriliantoni (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the level of management and educational efficiency in an educational institution through the measurement of teachers’ and education personnel’s perceptions. The research method uses a quantitative approach with a closed-ended questionnaire instrument based on a Likert scale. A number of respondents completed the questionnaire, which consists of 35 indicators covering human resource management, infrastructure efficiency, learning effectiveness, administrative digitalization, work culture, leadership, and technological transformation. The analysis results show that the level of management and efficiency falls into the “good” category, with average scores ranging from 3.80 to 4.35. The indicator with the highest score is collaborative work culture (4.35), while the indicator that still requires improvement is efficiency as a key indicator of quality (3.77). These findings confirm that the educational institution has a strong management foundation but needs further reinforcement in integrating efficiency as a core culture in decision-making.